Effective Factors in Medical Students' Willingness to Communicate in The Course of English for Specific Purposes - Giti Karimkhanlooei; Nima Motamed; Hamid Gharebaghi (Journal of Medical Education Development, 2022)
Background & Objective: It is argued that students have less tendency to communicate in English classes even after several years of attending language courses. The general objective of this research was to find the effective factors for willingness to communicate in English across medical classes. Materials & Methods: The participants in this study were 252 medical students from Zanjan University of Medical Sciences who were majoring in one of the fields of dentistry, medicine and pharmacy and were taking the course of English for Specific Purposes. Macintyre’s Willingness to Communicate questionnaire was used to compile the data. After collecting the data using the questionnaire, they were processed in the statistical package. The collected data were then tabulated and analyzed via SPSS (20) and AMOS. Results: In the structural model, there were significant pathways between self-confidence and motivation and WTC in ESP classes. Motivation had a positive effect on self-confidence. The teacher's immediacy, with its negative impact on shyness, increased the motivation to communicate in the ESP class. On the other hand, the paths of shyness to motivation and self-confidence were negative. All pathways were significant at 0.05. Conclusion: The findings of this study showed that, as in the previous studies, the tendency to communicate in language classes depends on several variables. Given that communication and speaking are the most important language skills, language learning planning is recommended to consider the importance of this skill. Language teachers should create conditions with low anxiety to encourage learners to speak and communicate. Shyness was another variable during the study that had a negative effect on the WTC. The results of this study also emphasize that highly motivated learners are more likely to participate in classroom activities and communication due to their self-confidence. Also, in this study, the teacher's intervention had a positive effect on reducing anxiety. Thus, it is recommended that teachers play an important role in motivating students to communicate I ESP classes.